Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Asli Daerah (PAD) (Studi Pada Pemerintah Kabupaten Kudus Periode Tahun 2008-2015) - Fatchur Rohman; Widya Sofiana (Accounting Study Program, Faculty of Economics and Business, 2017)
This study aims to determine and analyze whether the results of the collection of hotel taxes, advertisement taxes, parking taxes, and street lighting taxes have an effect on local revenue in the Kudus district government. The research method used in this study is a quantitative method, with multiple regression testing by doing the classical assumption test and t-test. The variables in this study are Hotel Tax (X1), Advertising Tax (X2), Parking Tax (X3), and Street Lighting Tax (X4) as the independent variable, and Local Revenue (Y) as the dependent variable. The data used is secondary data from 2008 to 2015 obtained from the Regional Revenue, Finance, and Asset Management Agency. The results of this study prove that partially only Hotel Tax and Street Lighting Tax have a significant positive effect on Regional Original Income, while Advertising Tax and Parking Tax have no significant effect on Regional Original Income in the Kudus Regency Government.